¿QUÉ HACEMOS CON NUESTRO HOTEL? - Llosa de Cárdenas, Fernando (1997)
Case study of a luxury hotel built in downtown Cusco in the late 1940s, when tourism in that city gained great momentum due to the global spread of the archaeological heritage located nearby. The business was success, but in the 1970s demand and revenues began to decline. The situation did not improve until 1993, when after years of accumulated debts, the hotel began to recover income, which allowed it to stay without major investments. Shortly after, the owner passed away, leaving a dilapidated hotel for his three sons. Now they must decide what to do with the hotel: sell it, rent it or operate it themselves or in association with another company. Unable to reach an agreement, they hire specialist consultants in the field to make a better decision. The case includes financial information and a summary of the consulting firm's study.